Analysis of the Success of the Educator and Educational Personnel Needs Analysis Management Information System Application (Simak-PTK) Using the DeLone and McLean Information System Success Model - Nurhayani, Siti (Journal Research of Social Science, Economics, and Management, 2026)
This study aims to evaluate the success of the use of the Educator and Education Personnel Needs Analysis Management Information System Application (SIMAK-PTK) using the DeLone and McLean model. The SIMAK-PTK application is used for the collection and processing of data on the position analysis of educators and education personnel which will be used to determine how much educators and education personnel are needed in each school. This study involved 100 respondents consisting of Principals, Vice Principals for Curriculum and School Operators, analyzed using a quantitative approach using the SEM PLS method. Of the 9 hypotheses tested, 7 hypotheses were accepted and 2 hypotheses were rejected. These findings make a theoretical and practical contribution to optimizing the strategic use of technology in the field of education.